2016
DOI: 10.1111/vsu.12477
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Complicated Orbital Depression Fracture with Medial Wall and Globe Repositioning in a Horse: A Collaboration Across Disciplines and Specialties

Abstract: Efforts to restore the medial wall and/or floor of the orbit with concurrent globe repositioning should be considered in horses with severe orbital depression fractures that result in abnormal globe position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Three previous reports have demonstrated successful cosmetic outcomes of periorbital fractures following plate fixation, using a cuttable bone plate, T-plate, and resorbable plate and tissue expanders. 5,13,14 This case report illustrates the repair of a displaced, comminuted fracture of the right zygomatic process, using a 2.7-mm LCP, which to the authors' knowledge, has not been reported before. LCPs have been used successfully for a variety of fractures 15 and allow complete load bearing across the fracture gap without relying on bone-to-plate friction for stability, subsequently able to withstand higher loads than other plates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Three previous reports have demonstrated successful cosmetic outcomes of periorbital fractures following plate fixation, using a cuttable bone plate, T-plate, and resorbable plate and tissue expanders. 5,13,14 This case report illustrates the repair of a displaced, comminuted fracture of the right zygomatic process, using a 2.7-mm LCP, which to the authors' knowledge, has not been reported before. LCPs have been used successfully for a variety of fractures 15 and allow complete load bearing across the fracture gap without relying on bone-to-plate friction for stability, subsequently able to withstand higher loads than other plates.…”
Section: Discussionmentioning
confidence: 84%
“…Tension‐band wiring is frequently used in periorbital fractures, but is unlikely to provide adequate support for comminuted fractures. Three previous reports have demonstrated successful cosmetic outcomes of periorbital fractures following plate fixation, using a cuttable bone plate, T‐plate, and resorbable plate and tissue expanders …”
Section: Discussionmentioning
confidence: 99%
“…Cases of orbital fractures involving the temporomandibular joint have been described previously. 12,19 The determination of the percentage of true clinical orbital fractures involving the temporomandibular joint would require a retrospective study on naturally occurring orbital fracture configurations. However, clinicians should consider temporomandibular articulation injury such as fractures and fissures in orbital fractures.…”
Section: Discussionmentioning
confidence: 99%